Development and Method Validation of Analysis of Urushiol in Sumac and Food Ingredients in Korea. (23rd November 2019) - Seo, Dongwon; Kim, Kijin; Choi, Hee-Don; Yoo, Miyoung; Ha, Jaeho; Lee, Kwang-Won
Abstract: This study developed an analytical method to determine the urushiol content in sap and several foods. The full process for urushiol analysis consists of extraction, trimethylsilyl silylation, analysis, and identification via GC-MS, with each step optimized to attain the required accuracy and precision. Urushiol was separated from sap via liquid–liquid extraction and was derivatized via silylation. The components were analyzed using a polar capillary column and identified using GC-MS. The deviations of relative retention times and retention time windows were within 0.001 and 0.02 min, which satisfied the criteria of 0.06 and 0.03 min, respectively. The response of the urushiol standards tested was found to be linear in the investigated concentration range, with a correlation coefficient of 0.998. The LODs were between 1.74 and 2.67 μg/mL.